(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research is devoted to analyzing how the image of “youth” is interpreted in Uzbek national literature and oral creative traditions. The article examines the artistic expression of the concept of youth through classical and contemporary literary works and samples of folk oral creativity. The research results revealed that the youth image is formed through the prism of national mentality, spiritual values, and cultural traditions. The “youth” image manifests as a multifaceted concept expressing not only biological age but also spiritual state, hope, and aspiration for the future.